Birds in Limbo - Kessler, Adriana; Arden, Anna; Klüger, Jessica; Goller, Laura; Ibrahim, Mina; Branković, Slađana; Jabaly, Tasnim; Okacha, Amro; Justus Liebig University Giessen (My University, 2026)
"Birds in Limbo" is a collaborative artwork by MeDiMi Research Associates in conversation with Egyptian comic artist Amro Okacha. Over five months, we met through a series of workshops to share experiences and shape the narrative of the project. The output brings together fieldwork and archival work, but it starts from lived experiences. Drawing on encounters across different German cities, in streets, markets, institutions, and homes, the work reflects the many "limbos" that shape migrant lives. It is built as a collage of stories, some lived by MeDiMi researchers, others shared by the people we work with. What comes through are everyday realities shaped by violence, displacement, bureaucracy, and time, and by the constant work of navigating all of this.
Keywords: Migration; Menschenrechte